Tingkat Literasi Digital Mahasiswa Pengguna Aplikasi E-Library Universitas Islam Negeri Raden Fatah - Satria Wijaksana, Muhammad Dewa; Herlina, Herlina (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2025)
Digital literacy competency is the ability to process various sources of information based on digital technology, understand the information obtained, and communicate information in digital format. This research seeks to answer the problem formulation in this research, namely: "what is the digital literacy level of students using the Universitas Islam Negeri Raden Fatah E-Library application?". This research is quantitative research with a descriptive approach. Data collection techniques in this research are observation techniques, questionnaires and documentation techniques. The data analysis technique in this research uses descriptive analysis techniques. The respondents in the research were 196 students using the Universitas Islam Negeri Raden Fatah E-Library application. The results of this research show that the mean of the results of calculating the digital literacy level of students using the Universitas Islam Negeri Raden Fatah E-Library application is at a score of 3.25 with a score range on a scale of 2.52 until 3.27. Thus, it can be concluded that the digital literacy level of students using the Universitas Islam Negeri Raden Fatah ELibrary application is in the high category.